Price and investment dynamics: Theory and plant level data - Magnus Lundin; Nils Gottfries; Charlotte Bucht; Tomas Lindström (Uppsala University, Department of Economics, 2007)
We construct a model of a firm competing for market share in a customer market and making investments in physical capital. The firm is financially constrained and there are implementation lags in investment. Our model predicts that product prices should depend on costs and competitors' prices, but respond weakly to demand shocks. Also, prices should be strongly related to investment. Estimating price and investment equations on panel data for Swedish manufacturing plants we find results which are qualitatively in line with these predictions, though the relation between investment and prices is stronger than predicted by our model.
Keywords: D43; E31; E32; E44; L11; L13; L16; 330; price rigidity; price equation; investment equation; credit constraint